(3eaGJM GdCSQGQs - (3CMeO Hf jhSa Hf GdceGO, CHh GdYHGSs ((3eMeO Hf Ydi GdHbGQ s)
(3ChdgG (B:s
(3GdaUd GdYGTQ ai cjajI GQJHGW ecK GdGLfI ai GdGMTGA HGdMQcGJ GdbeQjI heGjNUgG ef GdGOhGQ GdReGfjI s
(3BNQgG (B:s
(3aEf NQLJ GdWhGdY Ydi eG PcQfGg BfakG UfYJgG HgG ef UfGYI GdJYOjd eKd eG JbOe GfJgi GdaUd GdNGeS YTQ hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3HOGNdgG LOGhds
(3cJHJ gPg GdfSNI HQSe eMeO Hf Ydi Hf EOQjS Gdcheis
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs